"Teamwork cooperation": Nurse’s experience of cardiac arrest nursing care - Arif Wahyu Setyo Budi; Yati Afiyanti; Yustan Azidin (Malahayati International Journal of Nursing and Health Science, 2019)
Background : Emergency conditions are conditions that occur suddenly and are very life-threatening, so help must be given quickly, precisely and correctly. One of the life-threatening conditions is cardiac arrest, which is a condition where the heart cannot function anymore, and requires collaboration between health personnel in providing help and this always ends in death. The incidence of cardiac arrest at the Ulin Regional General Hospital during May to June 2017 was 88 cases and most of the deaths occurred in patients. Cardiac arrest can still be saved by the correct nursing care process so that return of spontaneous circulation can occur.Purpose : Identify and explore the experience of nurses doing nursing care for cardiac arrest.Methods: This type of research is qualitative with a phenomenological approach. The number of participants in this study were 9 nurses in the emergency room and intensive care unit. The process of retrieving data using interview guides, and data analysis using Colaizzy.Results: This study obtained a major theme, "Collaborative Teamwork" when providing nursing care for cardiac arrest. This theme was formed from two sub-themes namely "division of job teams", "collaboration" and KIE to the patient's family.The participant describing the existence of maintained teamwork can help smooth the process of nursing cardiac arrest so that patients can return to the condition of return of spontaneous circulation.